tính hợp lí
59.37-59.83-46.41
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1/ Ta có :\(-43.92-46.27+46.41\)
\(=\left(-86\right).46-46.27+46.41\)
\(=46.\left(-86-27+41\right)\)
\(=46.\left(-72\right)\)
\(=-3312\)
a) \(53.\left(-15\right)+\left(-15\right).47=\left(-15\right).\left(53+47\right)=\left(-15\right).100=-1500\)
b) \(\left(-43\right).92-46.27+46.41=\left(-86\right).46-46.27+46.41\)
\(=46\left[\left(-86\right)-27+41\right]=46.\left(-72\right)=-3312\)
c) \(\left(-72\right)\left(15-49\right)+15\left(-56+72\right)=\left(-72\right).15-72.49+15.\left(-56\right)+15.72\)
\(=\left[\left(-72\right).15+15.72\right]-72.49-15.56=0-3528-840=4368\)
d) \(\left(-2^4\right).17.\left(-3\right)^0.\left(-5\right)^6\left(-1^{2n}\right)=16.17.1.12625.\left(-1^{2n}\right)\)
a,\(53.\left(-15\right)+\left(-15\right).47\)
\(=-15.\left(53+47\right)=-15.100=-1500\)
\(b,-43.92-46.27+46.41\)
\(=-43.92-\left[46.\left(27-41\right)\right]=-43.92-\left[46.\left(-14\right)\right]\)
\(=-3956+644=-3312\)
\(c,-72\left(15-49\right)+15\left(-56+72\right)\)
\(=-15.72+49.72+15.\left(-56\right)+15.72\)
\(=72.\left(-15+49+15\right)-15.56=3528-840=2688\)
a) 53.(-15)+(-15).47
=53.[(-15)+(-15)].47
=53.(-30).47
=-1590.47
=-74730
\(\left(-2021\right).\left(23+76\right)-2021=\left(-2021\right).99-2021=-202100\)
\(5,-\dfrac{2}{7}-\left(\dfrac{5}{11}-\dfrac{9}{7}\right)+\dfrac{5}{11}=-\dfrac{2}{7}-\dfrac{5}{11}+\dfrac{9}{7}+\dfrac{5}{11}=\left(-\dfrac{2}{7}+\dfrac{9}{7}\right)-\left(\dfrac{5}{11}-\dfrac{5}{11}\right)=1-0=1\\ 6,\dfrac{2}{3}+\dfrac{-2}{5}+\dfrac{-5}{6}-\dfrac{13}{10}=\left(\dfrac{4}{6}+\dfrac{-5}{6}\right)+\left(\dfrac{-4}{10}-\dfrac{13}{10}\right)=\dfrac{-1}{6}+\dfrac{-17}{10}=\dfrac{-5}{30}+\dfrac{-51}{30}=\dfrac{-56}{30}=\dfrac{-28}{15}\)
\(7,\dfrac{-5}{9}+\dfrac{8}{15}+\dfrac{4}{-9}+\dfrac{7}{15}=\left(\dfrac{-5}{9}+\dfrac{-4}{9}\right)+\left(\dfrac{8}{15}+\dfrac{7}{15}\right)=\left(-1\right)+1=0\\ 8,\left(\dfrac{12}{13}+7\right)-\left(-\dfrac{1}{13}+8\right)=\dfrac{12}{13}+7+\dfrac{1}{13}-8=\left(\dfrac{12}{13}+\dfrac{1}{13}\right)+\left(7-8\right)=1+\left(-1\right)=0\)
a) \(\left(\dfrac{3}{8}-\dfrac{1}{5}-\dfrac{1}{3}\right)+\left(\dfrac{5}{8}-1\dfrac{3}{7}-\dfrac{4}{7}\right)+\dfrac{1}{3}\)
\(=\dfrac{3}{8}-\dfrac{1}{5}-\dfrac{1}{3}+\dfrac{5}{8}-\dfrac{10}{7}-\dfrac{4}{7}+\dfrac{1}{3}\)
\(=\left(\dfrac{3}{8}+\dfrac{5}{8}\right)+\left(\dfrac{-1}{3}+\dfrac{1}{3}\right)+\left(\dfrac{-10}{7}-\dfrac{4}{7}\right)-\dfrac{1}{5}\)
\(=1+0+\left(-2\right)-\dfrac{1}{5}\)
\(=-1-\dfrac{1}{5}\)
\(=\dfrac{-6}{5}\)
b) \(-24.\left(\dfrac{1}{3}-\dfrac{1}{4}\right)^2-1,5\)
\(=-24.\left(\dfrac{1}{12}\right)^2-\dfrac{3}{2}\)
\(=-24.\dfrac{1}{144}-\dfrac{3}{2}\)
\(=\dfrac{-1}{6}-\dfrac{3}{2}=\dfrac{-1}{6}-\dfrac{9}{6}=\dfrac{-10}{6}=\dfrac{-5}{3}\)
c) \(2^2-\left(-\dfrac{5}{7}\right)^0+\left(\dfrac{1}{3}\right)^4.3^6\)
\(=4-1+\dfrac{1}{81}.729\)
\(=4-1+9\)
\(=3+9=12\)
d) \(23\dfrac{1}{3}:\left(\dfrac{-5}{7}\right)+13\dfrac{1}{3}:\dfrac{5}{7}\)
\(=\dfrac{-70}{3}.\dfrac{7}{5}+\dfrac{40}{3}.\dfrac{7}{5}\)
\(=\dfrac{7}{5}\left(\dfrac{-70}{3}-\dfrac{40}{3}\right)\)
\(=\dfrac{7}{5}.\left(-10\right)\)
\(=-14\)
e) \(\dfrac{3}{4}.\dfrac{8}{5}+\dfrac{6}{15}:\dfrac{4}{3}-1\dfrac{2}{5}:1\dfrac{1}{3}\)
\(=\dfrac{3}{4}.\dfrac{8}{5}+\dfrac{6}{15}.\dfrac{3}{4}-\dfrac{7}{5}.\dfrac{3}{4}\)
\(=\dfrac{3}{4}\left(\dfrac{8}{5}+\dfrac{6}{15}-\dfrac{7}{5}\right)\)
\(=\dfrac{3}{4}\left(\dfrac{24}{15}+\dfrac{6}{15}-\dfrac{21}{15}\right)\)
\(=\dfrac{3}{4}.\dfrac{9}{15}\)
\(=\dfrac{9}{20}\)
a,
53.(-15) + (-15).47
= (-15).(53 + 47)
= -15.100
= -1500
b,
-43.92 - 46.27 + 46.41
= -43.92 - 46.(27 - 41)
= -86.46 - 46.(-14)
= 46.(-86 -14)
= 46.(-100)
= -4600
c,
-72(15 - 49) + 15(-56 + 72)
= -72.15 + 72.49 - 56.15 + 72.15
= 56(63 - 15)
= 2688
d,
(-24).17.(-3)0.(-5)6.(-12n)
= (-24).17.(-56)
= 4250000